Preparation of low-radioactive high-purity enriched 100MoO3 powder for AMoRE-II experiment - Yeon, Hyojin; Choe, JunSeok; Gileva, Olga; Hahn, Kevin Insik; Kang, Woon Gu; Kim, Go Woon; Kim, Hong Joo; Kim, Yena; Kim, Yeongduk; Lee, Eun Kyung; Lee, Moo Hyun; Leonard, Douglas S.; et al. (Frontiers in Physics, 2023)
This paper describes preparing radiopure molybdenum trioxide powder enriched with Mo-100 isotope for the AMoRE-II experiment. AMoRE-II, the second phase of the AMoRE experiments, will search for the neutrinoless double-beta decay (0DBD) of the 100Mo isotope using over 100 kg of 100Mo embedded in 200 kg of ultra-pure Li2100MoO4 bolometric crystals. Efficient purification technology was developed and adapted to purify 100MoO3 powder with a 5 kg per month production capacity. Based on the ICP-MS analysis of purified powder, the 232Th and 238U were reduced to < 9.4 Bq/kg and < 50 Bq/kg, respectively. The concentrations of potassium, transition metals, and heavy metals were lower than one ppm. HPGe counting confirmed the reduction of progenies from the 232Th and 238U decay chains, reporting upper limits of < 27 Bq/kg for 228Ac and < 16 Bq/kg for 228Th. The 226Ra activity was acceptable at 110  30 Bq/kg. In the last three years, 100 kg of pure 100MoO3 powder was produced. The production yield for the final purified product was above 90%, while irrecoverable losses were under 1.5%, and all by-products could be recycled further.